Формування виробничих структур у паливно-енергетичній галузі - Левшова, Ю.О. (Управління економікою: теорія та практика, 2013)
Визначено сутність та особливості формування виробничого потенціалу інтегрованих промислових компаній. Запропоновано загальну схему побудови раціональної виробничої структури на прикладі інтегрованої компанії енергетичної галузі України, розглянуто основні етапи процесу формування оптимальної виробничої структури. Определена сущность и особенности формирования производственного потенциала интегрированных промышленных компаний. Предложена общая схема построения рациональной производственной структуры на примере интегрированной компанииэнергетической отрасли Украины, рассмотрены основные этапы процесса формирования оптимальной производственной структуры. Specific ways and tools for improving the efficiency of integrated companies in a market economy are still the insufficiently investigated problem whose solution is of considerable interest not only fromthe point of view of control theory, but primarily in terms of practical value to domestic companies. In this context, the aim of this study is to determine the nature and peculiarities of the production potential of integrated industrial companies.Integrated production company represents a group of economically independent business entities related to production and technological and economic terms, leads to a joint economic activities on a contractual basis through the consolidation of assets, use of common resources, raw materials, fuel, energy, water, land, labor, facilities management and infrastructure support for a common strategic goal. Formation of an integrated production structure should be based not only on the achieved level of resources and the potential for the use of resources but on the synergy achieved at each stage of the chain of values. Production capacity of an integrated company means a set of tangible and intangible resources integrated into the existing system of technological, operational and organizational structures and device management, employees who have a specific organizational culture, skills and knowledge to meet the demands of consumers and the interests of the state and business partners.Proposed is the formation of an integrated production structure divided into the following stages: establishing the optimal number of manufacturers that are part of an integrated company, determining their capacity and comparison with a given output, determining the spatial location in the master plan of the formation of transport, communication and information and other relations within the company, building the infrastructure supporting the production structure to find product markets and form external traffic flows.